Analisis Pengaruh Kualitas Produk, Harga, Dan Kualitas Layanan Terhadap Keputusan Pembelian (Studi pada Rumah Makan Noroyono Purwodadi) - Mahfut, Ali, Lukman Hakim, S.E., M.Si (2016)
This study aims to determine whether the product quality, price and service quality influence on purchase decisions at Restaurant Purwodadi Noroyono and analyze the most dominant factor in influencing purchase decisions on Eating Noroyono Purwodadi. The population in this study is the consumers who buy at Restaurant Purwodadi Noroyono. Samples taken as many as 100 respondents using accidental sampling technique, the sampling technique based on chance, ie who happened to meet with the investigator can be sampled as it sees fit. Based on the research results, obtained the following regression equation: Y = 7.426 + 0.332 X1 - 0.162 0.430 X2 + X3 + e. Based on statistical data analysis, indicators in this study are valid and are reliable variables. In the classic assumption test, regression model multicoloniarity free, does not occur heteroskedastisitas, and normal distribution. The sequence individually on each of the most influential variable is the variable quality of service with a regression coefficient of 5.188 with sig. 0,000 smaller than 0.05. Then the variable quality of the product with a regression coefficient of 3.569 with sig. 0.001 less than 0.05. While the variables that significantly negative influence is the price with a regression coefficient of -1.994 with sig. 0,049 smaller than 0.05. Eating Noroyono Purwodadi need to retain the elements that have been rated by customers as well as the need to fix the things that are lacking. Key words: quality of product, price, quality of service, purchasing decisions.